2021
DOI: 10.1177/01626434211004450
|View full text |Cite
|
Sign up to set email alerts
|

A Technology-Based Self-Monitoring Intervention for Secondary Students with High-Incidence Disabilities

Abstract: Secondary students with high incidence disabilities who also display disruptive behaviors struggle to be successful in general education settings. As a result, general education teachers are looking for ways to utilize technology to provide them with opportunities to implement evidence-based interventions in their classrooms. In this study, teachers used MoBeGo, an iPad application, in a single-case withdrawal design (ABAB), to implement self-monitoring in high school general education classrooms with four stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Lastly, self-monitoring’s efficacy base is not limited to students with ASD. Self-monitoring can also meet the needs of postsecondary students with other disabilities such as attention deficit hyperactivity disorder, intellectual disability, or learning disabilities (Diegelmann & Test, 2018; Kumm et al, 2021). However, additional research is needed to evaluate this approach not only with college students with ASD but other disabilities as well.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, self-monitoring’s efficacy base is not limited to students with ASD. Self-monitoring can also meet the needs of postsecondary students with other disabilities such as attention deficit hyperactivity disorder, intellectual disability, or learning disabilities (Diegelmann & Test, 2018; Kumm et al, 2021). However, additional research is needed to evaluate this approach not only with college students with ASD but other disabilities as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies now demonstrate how technology-based modalities can enhance teacher implementation of standard classroom interventions [43][44][45]. Two past studies have demonstrated that when given access to interactive technology, a sizable percentage of teachers (39% to 51%) were able to develop a classroom intervention (i.e., a daily report card), implement it for one to two months, and produce meaningful change in student behaviors with minimal support from others [46,47].…”
Section: The Maximize Platformmentioning
confidence: 99%
“…Technology-based self-monitoring has developed rapidly over the last decade (Chia et al, 2018), with the use of mobile and web applications which allow students to record their behavior on phones, tablets, and laptops (e.g., Wills & Mason, 2014). This form of self-monitoring provides a unique advantage over traditional pen-and-paper based self-monitoring in the collection of monitoring data within software which can then be graphically displayed to allow for simple and efficient progress monitoring and data-based decision making (Kumm et al, 2021). Similar to the recent findings regarding the benefit of technology-based interventions to support academic skills (Kiru et al, 2018), adaptive behavior (Delisio & Isenhower, 2020), and academic engagement (Shanley et al, 2020), the integration of technology into self-monitoring provides additional value to self-monitoring beyond the effect of the intervention (Crossland & Dunlap, 2012).…”
Section: Increasing On-task Behavior Using Technology-based Self-moni...mentioning
confidence: 99%
“…First, technology-based self-monitoring has the benefit of being integrated into existing instructional technology (e.g., tablets or laptops), allowing for covert and efficient self-monitoring during instructional or adaptive tasks in inclusive settings (Crossland & Dunlap, 2012). Second, the streamlined process of monitoring, collecting, and graphing data on an electronic database eases instructional preparation demands on educators and enables sharing of information across special education team members (Kumm et al, 2021).…”
Section: Increasing On-task Behavior Using Technology-based Self-moni...mentioning
confidence: 99%